1995
DOI: 10.1247/csf.20.81
|View full text |Cite
|
Sign up to set email alerts
|

Hemocytes Release Phenoloxidase upon Contact Reaction, an Allogeneic Interaction, in the Ascidian Halocynthia roretzi.

Abstract: Keywords: allogeneic recognition/ascidian hemocyte/phenoloxidase/respiratory burst/exocytotic burst/superoxide anion ABSTRACT. Contact reaction is the morphological expression of allogeneic recognition by hemocytes in the ascidian, Halocynthia roretzi', namely they undergo an exocytotic burst upon contact with non-self (allogeneic) hemocytes in vitro. Wehave found that contact reaction is accompanied by a burst of cyanide-insensitive oxygen consumption that, unlike exocytotic events of mammalianphagocytes, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…Odiphenol compounds, oxidized by the PO system, take part in crosslinking of protein substrate and thus tan the upper layer of tunic (9,15,28). They also participate in self/nonself recognition reactions; in all biological reactions involving morula cells the latter form an extracellular matrix consisting of proteins stabilized by the PO system (2,5,9,12). The main proteins of the morula cells observed in this work may be precursors of the proteins tanned by phenols during PO reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odiphenol compounds, oxidized by the PO system, take part in crosslinking of protein substrate and thus tan the upper layer of tunic (9,15,28). They also participate in self/nonself recognition reactions; in all biological reactions involving morula cells the latter form an extracellular matrix consisting of proteins stabilized by the PO system (2,5,9,12). The main proteins of the morula cells observed in this work may be precursors of the proteins tanned by phenols during PO reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Oneof the main defense and/or recognition systems of many groups of invertebrates is the phenoloxidase system (PO system) (30,31). Ascidians use the PO system not only for defense reactions but for the sclerotization ofproteins in tunic (2,4,5,9,12,20,28). This system in ascidians is localized in the morula cells which seems to be a characteristic type for ascidians of all three families of the order Stolidobranchia (8,10,16,17,35).…”
mentioning
confidence: 99%
“…According to previous studies (Fuke, 1980;Fuke and Nakamura, 1985;Sawada and Ohtake, 1994;Akita and Hoshi, 1995), the alloreactivity of H. roretzi hemocytes may be determined by genetics. In the solitary ascidians, these alloreactivity among allogeneic hemocytes are observed only in Halocynthia roretzi.…”
Section: Correlation Between Alloreactivity and Tunic Colormentioning
confidence: 91%
“…PO is released in the contact reaction of H. roretzi hemocytes (Akita and Hoshi, 1995). H. roretzi hemocytes released PO in response to sheep red blood cells or yeast cells, and PO showed antibacterial activity in the presence of plasma of H. roretzi (Hata et al ., 1998).…”
Section: Future Investigationsmentioning
confidence: 99%
“…In ascidians, a key group in chordate phylogenesis (Swalla et al, 2000;Zeng and Swalla, 2005;Delsuc et al, 2006), POs are involved in inflammation and cytotoxicity against foreign cells or molecules (Akita and Hoshi, 1995;Cammarata et al, 1997Cammarata et al, , 2008Ballarin et al, 2005;Hata et al, 1998;Shirae and Saito, 2000;Shirae et al, 2002;Parrinello et al, 2003). The ascidian POs are copperdependent orthodiphenoloxidases (Kahn, 1985;Sugumaran et al, 1988) that were at first identified by histochemical reaction in the tunic hemocytes (Barrington and Thorpe, 1968), suggesting a quinone-tanning system involved in the production of tunic scleroprotein (Chaga, 1980).…”
Section: Introductionmentioning
confidence: 99%